Sosialisasi dan Pendampingan Public Speaking dan Pembentukan Organisasi Sebagai Upaya Pengembangan Sumber Daya Manusia Bagi Remaja SMP Negeri 4 Kutacane - Fitra Jaya (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
Competency/ability of Human Resources is also important in supporting the achievements and goals of the organization, in facing the rapid development of technology, organizations can no longer stand idly by, they will be crushed by the times, in the current era it could be said that people or organizations cannot sleep. amidst the hustle and bustle of development in all fields, the availability of highly skilled human resources is very necessary, the era of one-touch one service requires the ability to manage well, continuously, and consistently. To produce good human resources, implementing the 12-Year Compulsory Education program or graduating from high school is one of the government's efforts to improve the quality of human resources that are more qualified and competitive. Through this program, it is also hoped that it will be able to become a solution in reducing unemployment rates, reducing school dropout rates, and increasing the abilities of the young generation who are ready and able to compete globally. The method used in this service is public speaking assistance and the formation of youth organizations. The results of this research show that teenagers from SMP 4 Kutacane already understand: exploring self-potential, step-by-step building self-confidence, public speaking, character education, and organizing. Apart from that, there are changes and increases in knowledge and the addition of teenagers in organizations, and they tend to have the courage to express opinions in public, with public speaking training